Void fraction distribution for convective boiling flows in single and multiple heater rods assembly. (16th January 2022) - Yadav, Ashutosh; Roy, Shantanu
Highlights: Void fraction measurements for flow behavior mimicking the Boiling Water (nuclear) Reactor. Experimental measurements performed on three heater rods configuration at fixed electrical power. Measurements done using gamma-ray densitometry at varying inlet liquid flow rates and temperatures. Data reported here are useful for the development of CFD models for phase change in flowing liquids. Abstract: Void fraction distribution is an essential parameter for the design and development of nuclear reactors. In this work, void fraction measurements have been performed on an experimental setup mimicking the flow behavior in a calandria of Boiling Water Reactor (BWR). Experimental measurements for void fraction distribution were performed on three heater rods configurations at fixed electrical power using non-invasive gamma-ray densitometry at varying inlet liquid flow rates and temperatures. The main focus of this contribution was to measure void fraction distribution of boiling flows in a test section having the arrangement to accommodate different heater rods configurations by keeping the mechanical aspects of the gamma-ray densitometry technique simple. Measurements were done at four axial locations. and at each axial location, void fraction measurement was performed at eight radial locations. Experimental results show that void fraction profiles are not only influenced by the configuration of heater rods but also by the operating conditions. The void fraction profiles of configuration A were flat as compared to all other heater rod configurations. The data reported here help develop CFD models and understand the dependence of void fraction distribution on heater rods configuration.